Defense Economic Diplomacy in Overcoming the Impact of the Israel - Hamas War on Indonesia's Economic Resilience - Yulivan, Ivan; Mahroza, Jonni; Rianto, Rianto; Prakoso, Lukman Yudho; Setiadi, Muhammad Ikmal (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the most real threats from the increasingly heated Hamas-Israel conflict is the soaring world crude oil prices. Geographically, the proximity of the conflict in the Middle East is quite close to oil-producing countries. If the supply or distribution of oil from this area is disrupted. A significant increase in oil prices in a short time can have a tremendous shock effect on the market, the impact of this increase in commodities will spread to the national economy. This research was conducted using descriptive analysis. The process of Israel's annexation of Palestine will be described and analyzed in detail. The Indonesian government, through the first paragraph of the preamble to the 1945 Constitution, has the obligation to realize world peace by creating a new environment free from sovereignty conflicts, and clear and well-defined authority over economic activities that can take the Palestinian economy further towards the path of higher development and growth. Playing a direct diplomatic role by becoming the fifth of four countries currently the main actor in maintaining peace in the Middle East.